STRATEGI PENGELOLAAN GREY LITERATURE PADA PERPUSTAKAAN PERGURUAN TINGGI DI ERA DIGITAL: STUDI PUSTAKA - M. Adrian Nastiar; Friska Melinda; Selsa Farizer (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2026)
This study aims to formulate a comprehensive and digital technology-based management strategy for grey literature in university libraries. Grey literature plays a vital role in the scholarly communication ecosystem; however, its non-commercial publishing nature makes it more challenging to identify, access, and manage compared to conventional literature. This research employs a literature review method with a content analysis approach toward various scientific journal articles published within the last 10 years from academic databases. The results indicate that optimizing grey literature management in the digital era can be achieved through the implementation of four integrated primary strategies: (1) digitalization and media conversion to expand accessibility; (2) the development of structured, user-centered institutional repositories; (3) metadata standardization to ensure interoperability and ease of information retrieval; and (4) the implementation of accessibility policies based on Open Access to minimize legal and financial barriers. In conclusion, these four strategic pillars complement each other in forming a comprehensive management ecosystem, enabling university libraries to maximize their role as central hubs for information dissemination that supports research and inclusive scholarly communication.